2007
DOI: 10.1063/1.2790078
|View full text |Cite
|
Sign up to set email alerts
|

Type II InAs∕GaSb strain layer superlattice detectors with p-on-n polarity

Abstract: We report on high operating temperature midwave infrared detectors based on type II InAs∕GaSb superlattices (SLs) with a p-on-n polarity. All InAs∕GaSb SLs photodiodes reported so far have a n-on-p polarity with a thin InAs n-type top contact, that is incompatible with most present day readout integrated circuits. Current-voltage measurements reveal dark current densities of ∼5×10−7A∕cm2 (82K) and 0.18A∕cm2 (240K) at −0.1V. R0A products were equal to ∼1×105Ωcm2 (82K) and 0.24Ωcm2 (240K). Zero-biases D* were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Type-II InAs/GaSb superlattices (SL) photodiode is under development as a possible alternative technology for high performance infrared (IR) imaging systems [1] in the Mid-Wave IR (MWIR 3-5 lm) spectral windows [2][3][4][5][6][7][8], competing with the currently dominant MWIR detector technologies based on HgCdTe and InSb materials. However, to enhance the device performances, a better knowledge of electrical properties [9], carrier-lifetime [10], residual background carriers [11], and noise measurements of SL photodiode [12] are still necessary in the MWIR domain.…”
Section: Introductionmentioning
confidence: 99%
“…Type-II InAs/GaSb superlattices (SL) photodiode is under development as a possible alternative technology for high performance infrared (IR) imaging systems [1] in the Mid-Wave IR (MWIR 3-5 lm) spectral windows [2][3][4][5][6][7][8], competing with the currently dominant MWIR detector technologies based on HgCdTe and InSb materials. However, to enhance the device performances, a better knowledge of electrical properties [9], carrier-lifetime [10], residual background carriers [11], and noise measurements of SL photodiode [12] are still necessary in the MWIR domain.…”
Section: Introductionmentioning
confidence: 99%
“…High performance InAs/GaSb T2SL detectors have been reported for the mid-wave infrared (MWIR), 22,23,38 long-wave IR (LWIR), 5,7,32 and very long wave IR (VLWIR) 37 However, the performance parameters of T2SL detectors, in particular, the dark current densities, are still lower compared with the MCT benchmark (em Rule 07). 25 To realize T2SL-based focal plane arrays (FPAs) with high resolution the number of FPA pixels needs to increase with simultaneous scaling of the lateral dimensions of individual pixels.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups within the last years have reported on IR cameras for mid-wave IR (MWIR) and long-wave IR (LWIR) spectral ranges [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%